A nationwide survey of Antimicrobial Stewardship in Pediatric Intensive Care Unit: implementation notes from the Brazilian underground - Eliane Carlosso Krummenauer; Henrique Ziembowicz; Mara Rubia Santos Gonçalves; Magda Machado de Miranda Costa; Mariana Portela de Assis; Viviane Maria de Carvalho Hessel Dias; Cláudia Fernanda de Lacerda Vidal; Rochele Mosmann Menezes; Jane Dagmar Pollo Renner; Marcelo Carneiro (Antimicrobial Stewardship & Healthcare Epidemiology, 2023)
A multicenter diagnostic study was conducted to investigate the implementation of an Antimicrobial Stewardship Program in Brazilian Pediatric Intensive Care Units. The analysis unveiled the main implementation impediments of the Antimicrobial Stewardship Program such as the lack of professionals and resources available to the program.